2011
DOI: 10.1007/s12011-011-9239-y
|View full text |Cite
|
Sign up to set email alerts
|

Serum Mercury Level and Multiple Sclerosis

Abstract: Exposure to heavy metals has been associated to a higher incidence of multiple sclerosis. In this work, we present a possible relationship between serum mercury levels and development of multiple sclerosis in Isfahan, the third largest city in Iran. Seventy-four patients affected by multiple sclerosis were retrieved from multiple sclerosis (MS) clinic in Isfahan, Iran. By matching sex and age, 74 healthy volunteers were chosen as control group. Blood samples were collected and serum mercury content was determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…Low exposure to mercury has been reported to play a role in immune system dysregulation [12, 13] . It may trigger autoimmune diseases such as systemic lupus erythematosus and multiple sclerosis [1416] . An aberrant immune response resulting in inflammatory bowel disease-like lesions has been associated with mercury intoxication [12] .…”
Section: Discussionmentioning
confidence: 99%
“…Low exposure to mercury has been reported to play a role in immune system dysregulation [12, 13] . It may trigger autoimmune diseases such as systemic lupus erythematosus and multiple sclerosis [1416] . An aberrant immune response resulting in inflammatory bowel disease-like lesions has been associated with mercury intoxication [12] .…”
Section: Discussionmentioning
confidence: 99%
“…No environmental pollutant or toxicants have been investigated in CD, although environmental pollution is getting higher and higher in the last decades. Different studies demonstrated that Hg participates in the development of several immune disorders as membraneous nephropathy [ 43 ], autoimmune glomerulonephritis [ 44 ], Wegener's granulomatosis [ 45 ], scleroderma [ 46 ], systemic lupus erythematosus [ 47 ], pemphigus [ 48 ], and multiple sclerosis [ 49 ]. Epidemiologic data suggest that Hg amalgam fillings have an effect in the exacerbation and/or onset of multiple sclerosis [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Literature data concerning metal alterations in MS patients are partly contradictory and may depend on the biological specimens used for analysis (such as blood, serum, hair, urine, CSF, or post-mortem tissues from autopsy) making comparisons between studies of limited values. Several studies using atomic absorption spectrophotometry, the colorimetric method, or neutron activation analysis have reported altered metal levels in blood or serum from MS patients, such as decreased levels of zinc [132][133][134], increased levels of copper [135,136], increased levels of arsenic and lead [137,138], and increased levels of mercury [139] compared to healthy control groups.…”
Section: Metals In the Blood Or Serummentioning
confidence: 99%